PENGARUH KOORDINASI TERHADAP EFEKTIVITAS PELAYANAN PEMBUATAN IZIN MENDIRIKAN BANGUNAN (IMB) DI BADAN PELAYANAN PERIZINAN TERPADU (BPPT) KABUPATEN CIREBON - Isakandar Zulkarnaen; Mohammad Taufik Hidayat; Nursahidin Nursahidin (Jurnal Ilmiah Publika, 2013)
Thesis title is : "The Effect of Coordination on the Effectiveness of Development Services Building Permit ( IMB ) at the Integrated Licensing Service Agency ( BPPT ) Cirebon " . The problem that the authors make is less optimal effectiveness of service in the manufacture of building permit ( IMB ) , the above problem arises because allegedly caused by not optimal implementation of coordination between the Integrated Licensing Service Agency ( BPPT ) with the Department of Human Settlements and Spatial Cirebon , which look at the things that , because of the completion of the work Integrated Personnel Licensing Service Agency ( BPPT ) Cirebon was not in accordance with a predetermined time in providing services manufacture Building Permit ( IMB ) so that the emergence of public dissatisfaction . Achievement goals Integrated Licensing Service Agency ( BPPT ) Cirebon less well run and has not been fully achieved in providing services manufacture Building Permit ( IMB ) that there had been complaints that come from the community . Employees Integrated Licensing Service Agency ( BPPT ) Cirebon often make mistakes on the job of providing services manufacture building permit ( IMB ) . Statistical hypothesis that the authors propose is as follows : " There is a positive and significant influence on the effectiveness of service coordination manufacture of building permit ( IMB ) at the Integrated Licensing Service Agency ( BPPT ) Cirebon " . The research method that I use is the census and survey methods with quantitative analysis techniques , which analyzes the effect of variable to variable effectiveness of service coordination , supported by quantitative data through statistical data processing . The research proves that the coordination between the Integrated Licensing Service Agency ( BPPT ) with the Department of Human Settlements and Spatial Planning Cirebon in the manufacture of building permit ( IMB ) is not optimal , which only reached the level of success is quite good with a total score of 6157 or 56.3 % . Variable effectiveness of services also less achieved , still in the category of good enough or not optimal with a total score of 2458 or 55.17 % . There is a positive and significant effect among variables of the effectiveness of coordination of services , namely the strong category with a score of 0.774 and a count rs rs value table for the respondents were 81 people with a 95% confidence2level and 5 % error level of 0.220 with coefficient or coefficient determinant diterminan amounted to 59.9 % , it can be concluded that the results received .